Continuity of care for children with special healthcare needs during the COVID-19 pandemic - José Pinheiro Batista Medeiros; Eliane Tatsch Neves; Mardênia Gomes Vasconcelos Pitombeira; Sarah Vieira Figueiredo; Daniella Barbosa Campos; Ilvana Lima Verde Gomes (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To describe the continuity of care for children with special healthcare needs during the COVID-19 pandemic through the perception of their caregivers in the Northeast of Brazil. Methods: Qualitative descriptive-exploratory research carried out between June and September 2020, in a municipality in the Northeast of Brazil. Eleven caregivers participated through semi-structured interviews conducted at home. The data were submitted to thematic content analysis. Results: The social isolation period and the suspension of health services affected the continuity of care, configuring the category "Implications of the COVID-19 pandemic for the continuity of care". Caregivers expressed fear of children contracting the coronavirus, characterizing the category "Fears and uncertainties of the COVID-19 pandemic in view of the vulnerability of children with special healthcare needs". Final considerations: Caregivers' reports revealed problems in the continuity of care for the studied cohort. Therefore, health care practices must be rethought in times of pandemic.